In Situ Humidity Measurements at the CL Surface By MEMS-Based Sensors. (14th September 2015) - Tsujikawa, Jun; Minami, Ryotaro; Araki, Takuto
Abstract : Water management is essential for optimizing the performance of proton exchange membrane fuel cells, then for measuring the local humidity inside membrane electrode assembly (MEA), the thin film humidity sensors (TFHS) are fabricated by the micro-electro-mechanical systems (MEMS) based techniques. The sensor was placed between the catalyst layer (CL) and the microporous layer (MPL) at the cathode. The sensor thickness is only about 9 μm, and the slight effects on total cell performance were observed with the insertion of it. In-situ measurement with a humidity sensor showed the capacitance and RH increased with the increase of the current density linearly up to 0.3 A/cm 2 . The capacitance change became moderate the region more than 0.3 A/cm 2, because the relative humidity reached 100% at the 0.3 A/cm 2 and water started to accumulate.